Optimal state-feedback and proportional-integral controller performance comparison for DC-DC Zeta converter operating in continuous conduction mode - Sarkawi, Hafez; Yoshito, Ohta (2016)
A dc-dc zeta converter can be used to step-up or step-down input voltage. In order to stabilize the output voltage, a control subsystem needs to be deployed. This paper presents state-feedback controller for the dc-dc zeta converter using optimal control design technique. Performance comparison is made with proportional-integral (PI) controller. The system’s response subject to load perturbation is presented using PSIM® simulation tool. The proposed optimal control exhibits better control duty-cycle response thus better margin of stability compared to PI control.